2020
DOI: 10.1248/cpb.c19-00769
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Paramylon Particles Produced by <i>Euglena gracilis</i> EOD-1 Using FIB/SEM Tomography

Abstract: Euglena gracilis EOD-1, a microalgal strain, produces large quantities of paramylon, a class of polymers known as β-1,3-glucans and has been reported to function as a dietary fiber and to improve the metabolic syndrome including obesity. However, despite its importance, the morphometric analysis of paramylon has not been conducted so far. In this study, we attempted to observe the detailed three-dimensional structure of paramylon by focused ion beam/scanning electron microscopy (FIB/SEM). Paramylon samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It has been speculated that EOD-1PM is less susceptible to degradation by intestinal bacteria and is less likely to be absorbed through the intestines in mice [ 19 , 21 ]. Therefore, EOD-1PM may not be directly involved in improving serum antioxidant potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that EOD-1PM is less susceptible to degradation by intestinal bacteria and is less likely to be absorbed through the intestines in mice [ 19 , 21 ]. Therefore, EOD-1PM may not be directly involved in improving serum antioxidant potential.…”
Section: Discussionmentioning
confidence: 99%
“…Euglena gracilis is a kind of microalgae that produces a β-1,3-glucan called paramylon. E. gracilis EOD-1 containing a high proportion (70–80%) of paramylon is known to proliferate depending on culture conditions [ 18 , 19 ]. Moreover, E. gracilis EOD-1, which has been suggested to have various functionalities, has recently drawn attention as a health food.…”
Section: Introductionmentioning
confidence: 99%
“…At least six different morphological variations have been reported, from disks to rods (Monfils et al, 2011). For E. gracilis, the shape is typically flat cylindrical with reported diameters around 5m and thicknesses about 3 m (Anraku et al, 2020). The granules are actually surrounded by a biomembrane.…”
Section: ) Macromolecular and Crystalline Structure Of Paramylonmentioning
confidence: 99%
“…It is assumed that paramylon is first biosynthesized as elementary microfibrils with low crystallinity (Kiss et al, 1987(Kiss et al, , 1988: as the granule matures, the microfibrils assemble to form the final highly ordered crystalline structure with concentric deposition of aggregates of elemental nanofibers of 4-10 nm. Recently, morphometric characterizations by focused ion beam/scanning electron microscopy (FIB/SEM) tomography (Anraku et al, 2020) confirmed that the paramylon particles have a very dense structure without large void spaces. A specific surface area (SSA) of 2.438 m 2 /g was measured by BET which is close to starch granules from potatoes and corn.…”
Section: ) Macromolecular and Crystalline Structure Of Paramylonmentioning
confidence: 99%